Urban and Regional Development in China: Policy Innovation - Kardkarnklai, Yuwadee; Angasinha, Chatwarun (Journal of Dhamma for Life, 2025)
The success of economic growth in China has coincided with the rapid urbanization During the First Five-Year Plan (1953-1958), the urban population was only 13%. By 2023, it had increased to 66.2%. The size of cities has expanded and their numbers have grown significantly. Chinese cities are increasingly playing a more important role, which is leading to the study on China’s urban and regional development: policy innovation. The objectives of this study are: 1) to examine China’s urban development policies, 2) to explore the policy processes in urban and regional development in China and future trends, and 3) to identify policy innovations that China has applied in urban and regional development. This study employs a qualitative research method, analyzing context from statistical data, documents, research reports, and interview reports. Findings: China uses cities as an engine for driving the country’s economic growth, with the Five-Year Plans serving as guiding policy frameworks. These plans are tools used by the Chinese Communist Party to regulate the country development, and also serve as mechanisms to maintain continuity and stability in policies, ensuring progress toward desired goals. The first wave of urban development utilized policy tools for establishing economic development zones, leading to the second wave, which employed policy tools for city cluster development. The focus is on creating a balance between regional development and between rural and urban areas. In summary, China's urban and regional development demonstrates that China has created policy innovations, both as processes and tools, with a unique feature of the public administration system that still contribute to policy innovations at national and the local level.